A geometric phase analysis method dedicated to nanomaterials orienting along high-index zone axis. (October 2018) - Wang, Yan; Yu, Jieyi; Zhang, Xuefeng
Highlights: A GPA method using single lattice fringes. This GPA method is accurate and reliable in determining strain distributions. Defocus values influence the accuracy of strain measurements. Abstract: Strain within nanomaterials plays a crucial role in defining their physical and chemical properties. Geometrical phase analysis (GPA) was widely used to investigate deformation within nanomaterials. The traditional GPA method using geometric phases of two lattice fringes provides two-dimensional strain mapping, which is inapplicable to nanomaterials viewed along high-index zone axis. Herein using silicon nanoplate embedded in Si0.5 Ge0.5 matrix as a test object, we illustrate a GPA method using single lattice fringes. The availability of this GPA method was testified by comparison with traditional GPA method. This work presents an opportunity to extend application of the GPA method.